2023
DOI: 10.1186/s12886-023-02801-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of simultaneous vs sequential pars plana vitrectomy and cataract surgery

Abstract: Background To compare the clinical outcomes of patients undergoing sequential pars plana vitrectomy (PPV) followed by cataract extraction surgery (CE) [PPV/CE], simultaneous PPV and CE (PPV + CE), and sequential CE followed by PPV [CE/PPV]. Methods A retrospective observational cohort study of 427 eyes of 404 patients who underwent either sequential or simultaneous PPV and CE surgery between March 2016 and May 2021. Pre-operative and post-operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Until 6mo, the BCVA improvement in the combined group was significantly superior to that in the subsequent group. In this study, the mean difference in the BCVA improvement 6mo after PPV between the two groups was 14.50 letters, which was almost consistent with previous study results [21][22][23][24] . After the subsequent cataract surgery, no statistic difference was found between the two groups at 12mo, which also verified that the worsen visual prognosis at 6mo in the subsequent group was due to cataract aggravation and the surgical technique were comparable between the two groups.…”
Section: Safety and Adverse Eventssupporting
confidence: 92%
See 2 more Smart Citations
“…Until 6mo, the BCVA improvement in the combined group was significantly superior to that in the subsequent group. In this study, the mean difference in the BCVA improvement 6mo after PPV between the two groups was 14.50 letters, which was almost consistent with previous study results [21][22][23][24] . After the subsequent cataract surgery, no statistic difference was found between the two groups at 12mo, which also verified that the worsen visual prognosis at 6mo in the subsequent group was due to cataract aggravation and the surgical technique were comparable between the two groups.…”
Section: Safety and Adverse Eventssupporting
confidence: 92%
“…Moreover, simultaneous management of anterior and posterior segment pathologies can not only help patients achieve their best visual outcomes earlier but also reduce the number of surgeries and medical burdens. Several previous studies have been conducted, which demonstrated that the combined surgery was effective and gratifying, with optimal prognoses in patients with PDR and dense cataracts [21][22][23][24][25] . However, early lens extraction during PPV in patients with PDR and mild cataracts remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation